2008
DOI: 10.1590/s1516-35982008001200004
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de ovelhas e cordeiras em pastagem de azevém-anual sob níveis crescentes de suplementação

Abstract: RESUMO -Avaliou-se o comportamento ingestivo de ovelhas em lactação e cordeiras nos períodos pré e pós-desmama recebendo quatro níveis de suplemento (0; 0,5; 1,0 ou 1,5% do peso vivo), mantidas em pastagem de azevém (Lolium multiflorum Lam.) sob pastejo contínuo, em delineamento inteiramente casualizado, com medidas repetidas no tempo, com quatro tratamentos e duas repetições. O suplemento utilizado foi uma ração comercial fornecida diariamente às 14 h.Avaliaram-se os tempos diários de pastejo, ruminação, ócio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…According to these authors, the reduction in grazing time is the result of more time spent at the trough, which increases with the amount of supplement provided. Bremm et al (2008), working with sheep, also concluded that animals provided with an energyprotein supplement spent less time grazing and more time at the trough, despite not showing differences in the size and rate of bites. Averages followed by the same lower-case letter in the row and upper-case letter in the column do not differ by Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these authors, the reduction in grazing time is the result of more time spent at the trough, which increases with the amount of supplement provided. Bremm et al (2008), working with sheep, also concluded that animals provided with an energyprotein supplement spent less time grazing and more time at the trough, despite not showing differences in the size and rate of bites. Averages followed by the same lower-case letter in the row and upper-case letter in the column do not differ by Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 99%
“…Although the objective of using nutritional supplements is to increase animal performance, variations in pasture structure are often observed (Gomide et al, 2009;Bremm et al, 2008) as stocking rates increase (Roman et al, 2008), as a consequence of the substitutive or combined effects of supplementation, depending on the criteria adopted for regulating the management of animal stocking.…”
Section: Introductionmentioning
confidence: 99%
“…This is often associated with shorter grazing time, as shown by Bremm et al (2008) in meat sheep grazing Italian ryegrass in Brazil.…”
Section: Grazing Sheepmentioning
confidence: 99%
“…There is a contradiction in literature existent about the results of pasture management on animals´ response in change of time spent in other activities. In ryegrass plus oat the time spent in other activities by heifers proved to be similar, regardless of supplementation strategy (BREMM et al, 2008). On the other hand, Pellegrini et al (2011) reported that time spent in other activities was reduced to 0.90 minute per day during pasture utilization.…”
Section: Resultsmentioning
confidence: 97%
“…Supplemented grazing animals have their ingestion behavior altered. Supplemented heifers grazing on ryegrass reduce their grazing time and spend more time in other activities (BREMM et al, 2008). The decrease in grazing time is proportional to the amount of supplement provided, without any changes in rumination time (MACARI et al, 2007), or forage intake when compared to nonsupplemented animals (BREMM et al, 2005).…”
Section: Introductionmentioning
confidence: 99%